Special issue introduction: Sub-Saharan Africa's agri-food system in transition. Issue 2 (16th November 2015) - Kaneene, John B.; Haggblade, Steven; Tschirley, David L
Abstract : Purpose: – The papers in this special issue measure the pace of change and the employment consequences of rapid ongoing transformation of Sub-Saharan Africa's agri-food system. After quantitatively assessing the pace of change in consumer diets, a succession of papers examines the resulting change in public health, employment structure, job skill requirements and the educational challenges facing agricultural education and training (AET) institutions charged with preparing African youth with workforce skill required to succeed in the continent's rapidly changing, rapidly growing agri-food system. The paper aims to discuss these issues. Design/methodology/approach: – Changes in consumer demand and workforce skill needs emerge from a quantitative projection model using Living Standards Measurement Studies in half a dozen countries in Eastern and Southern Africa. Based on surveys of employers, graduates and staff at AET institutions in a range of 14 different countries, the analyses evaluate the workforce skill needs and educational challenges for preparing Africa's emerging youth bulge to seek productive careers on the farm and in post-farm segments of the agri-food system. Throughout, the papers contrast findings from countries at different stages in the food system transformation using a typology developed in this paper. Findings: – The concluding paper in this issue by Kabasa, Kirsten and Minde summarizes key findings emerging from this collection. Originality/value: – The contributions in this special issue report original research based on analysis of LSMS data and on interviews with agri-food system employers, agricultural education institutions and professionals in over a dozen African countries.